WAR: Democracy's Lengthened Hand - Andrian Willyan Djaja (Islamic Research, 2019)
Democracy and monarchy are often considered counterparts, and people tend to choose the free-will-conserving democracy rather than the stiff monarchy. The United States of America gives all they have to spread democracy to the world, even using militaristic way. It is obvious that America forces their democracy to be played by countries of the world, through the war as a way, and politics as another way. In short, war is just a tool for America to spread democracy to the whole world. Demokrasi dan monarki sering dianggap bertentangan, dan orang-orang cenderung memilih demokrasi yang mempertahankan kebebasan memilih daripada monarki yang kaku. Amerika Serikat berupaya keras untuk menyebarkan demokrasi ke seluruh dunia, bahkan menggunakan cara militer. jelas bahwa Amerika memaksakan demokrasi mereka untuk digunakan negara-negara di seluruh dunia, melalui perang sebagai salah satu cara, dan politik sebagai cara lainnya. Singkatnya, perang hanyalah salah satu cara yang digunakan Amerika untuk menyebarkan demokrasi ke seluruh dunia.